A.A. Vlasov, and N.N. Bogolyubov, the Forerunners of Quantum Electrodynamics - Rukhadze, A.A. (Відділення фізики і астрономії НАН України, 2010)
All written below is the child of my brain, although the meetings and discussions of these two great physicists actually took place, and these discussions resulted in the substantiation of the famous Vlasov equation in the seminal work by N.N. Bogolyubov “Dynamic Methods in the Statistical Physics” published in 1946. This work, together with Vlasov’s one, not only proved the statistical physics of many-particle systems with Coulomb interaction, but also laid the corner stone of the method of electrodynamic perturbation theory, which brought about the creation of quantum electrodynamics at the end of the 1940s. Все, що написано – плiд моєї фантазiї, хоча зустрiчi та дискусiї цих двох великих фiзикiв дiйсно мали мiсце. Цi дискусiї привели до обґрунтування знаменитого рiвняння Власова у видатнiй роботi М.М. Боголюбова “Динамiчнi методи в статистичнiй фiзицi”, яку було опублiковано в 1946 роцi. Ця робота разом iз роботою Власова не тiльки обґрунтувала статистичну фiзику багаточастинкових систем iз кулонiвською взаємодiєю, але й заклала основу методу електродинамiчної теорiї збурень, яка в кiнцi 40-х рокiв привела до створення квантової електродинамiки.